2017
DOI: 10.1093/nar/gkx195
|View full text |Cite
|
Sign up to set email alerts
|

Critical 23S rRNA interactions for macrolide-dependent ribosome stalling on the ErmCL nascent peptide chain

Abstract: The nascent peptide exit tunnel has recently been identified as a functional region of ribosomes contributing to translation regulation and co-translational protein folding. Inducible expression of the erm resistance genes depends on ribosome stalling at specific codons of an upstream open reading frame in the presence of an exit tunnel-bound macrolide antibiotic. The molecular basis for this translation arrest is still not fully understood. Here, we used a nucleotide analog interference approach to unravel im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
(113 reference statements)
3
29
0
Order By: Relevance
“…Of the CR mutants that were viable in vivo, there was no clear relationship between fold enrichment after RISE and cellular growth rate. Interestingly, the non-viable CR variants all contained mutations at the 2062 position, which is consistent with the previous observation that such mutations are lethal despite in vitro ribosome activity 32,35 . The result that ribosomes that are active in iSAT may be unable to support life demonstrates the potential of RISE to select ribosomes that are proficient at translating challenging templates or monomers in vitro without concern for viability in living cells.…”
Section: Resultssupporting
confidence: 90%
“…Of the CR mutants that were viable in vivo, there was no clear relationship between fold enrichment after RISE and cellular growth rate. Interestingly, the non-viable CR variants all contained mutations at the 2062 position, which is consistent with the previous observation that such mutations are lethal despite in vitro ribosome activity 32,35 . The result that ribosomes that are active in iSAT may be unable to support life demonstrates the potential of RISE to select ribosomes that are proficient at translating challenging templates or monomers in vitro without concern for viability in living cells.…”
Section: Resultssupporting
confidence: 90%
“…Of the CR mutants that were viable in vivo, there was no clear relationship between fold-enrichment after RISE and cellular growth rate. Interestingly, the non-viable variants all contained mutations at the 2062 position, which is consistent with the previous observation that such mutations are lethal despite in vitro ribosome activity 20,23 . The result that ribosomes that are highly active in vitro may be inviable in vivo demonstrates the potential of RISE for selecting ribosomes that are proficient at translating challenging templates or monomers without concern for in vivo viability.…”
Section: Resultssupporting
confidence: 90%
“…Biochemical, genetic, and structural studies have shown that the tunnel interacts with specific sequence motifs of nascent chains. These interactions may lead to translation arrest that regulates gene expression (Arenz et al, 2014;Bischoff et al, 2014;Chiba et al, 2011;Gong and Yanofsky, 2003;Koch et al, 2017;Nakatogawa and Ito, 2002;Ramu et al, 2011;Seidelt et al, 2009;Sohmen et al, 2015;Vazquez-Laslop et al, 2011;Woolhead et al, 2006).…”
Section: Introductionmentioning
confidence: 99%